Potentially fatal complications of new systemic anticancer therapies - Kovač-Blaž, Milena (Radiology and oncology (Ljubljana), 2024)
Various types of immunotherapy (i.e. immune checkpoint inhibitors ICIs, chimeric antigen receptor CAR T-cells and bispecific T-cell engagers BiTEs) and antibody drug conjugates (ADCs) have been used increasingly to treat solid cancers, lymphomas and leukaemias. Patients with serious complications of these therapies can be presented to physicians of different specialties. In this narrative review we discuss potentially fatal complications of new systemic anticancer therapies and some practical considerations for their diagnosis and initial treatment. Results Clinical presentation of toxicities of new anticancer therapies may be unpredictable and nonspecific. They can mimic other more common medical conditions such as infection or stroke. If not recognized and properly treated these toxicities can progress rapidly into life-threatening conditions. ICIs can cause immune-related inflammatory disorders of various organ systems (e.g. pneumonitis or colitis), and a cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) may develop after treatment with CAR T-cells or BiTEs. The cornerstones of management of these hyper-inflammatory disorders are supportive care and systemic immunosuppressive therapy. The latter should start as soon as symptoms are mild-moderate. Similarly, some severe toxicities of ADCs also require immunosuppressive therapy. A multidisciplinary team including an oncologist/haematologist and a corresponding organ-site specialist (e.g. gastroenterologist in the case of colitis) should be involved in the diagnosis and treatment of these toxicities. Conclusions Health professionals should be aware of potential serious complications of new systemic anticancer therapies. Early diagnosis and treatment with adequate supportive care and immunosuppressive therapy are crucial for the optimal outcome of patients with these complications.
Keywords: bispecifični vključevalec T-celic; imunosupresivna terapija; imunosupresivno zdravljenje; konjugat protiteles; potencialno smrtna toksičnost; T-celice himernega antigenskega receptorja; zaviralci kontrolnih točk